USING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN THE EDUCATION SECTOR: OPPORTUNITIES AND CHALLENGES IN ENGLISH LANGUAGE TEACHING (ELT) - Tira Nur Fitria (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This research explains the opportunities and challenges of using Information and Technology Communication (ICT) in the English Language Teaching (ELT) process. This research is library research. The analysis shows that educators (teachers/lecturers) have opportunities and challenges in adopting ICT in their classrooms. The development of ICT requires educators to adapt to the technology. The opportunities for using ICT in ELT are improving the quality of education, encouraging the development of new teaching methods, getting get unlimited ease of information easier, providing instant access to various learning resources, changing learning styles, making ELT activities more flexible, allowing teachers to use/create interesting learning media in teaching, having the potential to reduce the price of textbooks and education costs, increasing student learning interest and motivating students to learn. While, several challenges of using ICT in ELT are the emergence of various disturbances, growing lazy mindset, requiring expensive costs, limitations of social interaction between teacher and students, difficulty in understanding learning materials in digital form, having a dependence on technology, distracting students on ICT tools, and disconnect students from face-to-face relationships. Besides, other challenges are the teacher's self-confidence is lacking use of ICT, lack of teacher competence, teacher attitudes and inherent resistance against change, the teacher's level, and the institutional or school level, limitations in the field of access, limited time available to prepare ICT, limitations in self-potential development through training of using ICT. The infrastructure problem and limitations in technical support in terms of using ICT also influenced the challenges in ICT implementation.